The Effect of Service Quality on Customer Satisfaction in Makassar Jeans House Palu City - Fachrul Alfajar; Mustainah Mustainah; Muzakir Tawil (PINISI Discretion Review, 2020)
The purpose of this study was conducted to determine the Effect of Service Quality on Customer Satisfaction at Makassar Jeans House in Palu City. The type of research used is quantitative research with a type of comparative causal research. The sample in this study amounted to 100 Makassar Jeans House customers in Palu City. This study uses a theory (Zeithaml, 1988) where there are 5 (five) indicators to measure service quality which includes Tangibles, Reliability, Responsiveness, Assurance, Empathy. The results of this study indicate that the influence of service quality on customer satisfaction has a strong relationship with a correlation coefficient of 0.766, the results of this study also indicate that service quality simultaneously affects customer satisfaction, based on the results of the determination coefficient of service quality affects customer satisfaction by 58.7%, while the remaining 41.3% is influenced by other variables outside of this study.